First record of the mealy plum aphid Hyalopterus pruni (Geoffroy), (Homoptera, Aphidoidea) in Madeira Island - Ilharco, Fernando A. (2009)
Submitted by RUA REPOSITORIO (repositorio@uac.pt) on 2009-06-30T15:26:57Z No. of bitstreams: 1 pp_93_94_Ilharco_Soares_short_25.pdf: 127340 bytes, checksum: 3c269536e2f4c1ad03cbae19efabe407 (MD5)